The effect of targeted field investigation on the reliability of earth-retaining structures in passive state: A random field approach - Christodoulou, Panagiotis; Pantelidis, Lysandros; Gravanis, Elias (My University, 2020)
In one of their recent works, the authors examined parametrically the e ect of targeted field investigation on reducing statistical uncertainty in active state analysis of earth retaining structures based on 2165 di erent cases for each of the sliding and overturning modes of failure. This analysis indicates that the optimal sampling location is always adjacent to the wall, while a sampling domain length equal to the whole height of the wall is suggested to be considered. The present paper deals with the “symmetrical” problem of soil under the passive state of stresses. Working in a similar manner, 1879 passive state cases have been considered (also for each of the sliding and overturning modes of failure) in a Random Finite Element Method (RFEM) analysis framework, where soil properties are modeled as random fields while measurements are modeled by sampling from di erent points of the field domain. The “actual” resultant earth passive pressure force (or moment) exerted by the random soil on the retaining wall is compared against the respective “predicted” one calculated using the soil property values sampled from the random field. Failure is considered to have occurred when the derived “actual” force is smaller than the respective “predicted” force. This analysis clearly indicates that the passive state constitutes a di erent problem, where the optimal sampling distance from the wall is half the wall height. Regarding the depth of exploration, it was again found to be the entire wall height. In addition, the present analysis shows that, the benefit from a targeted field investigation is much greater than the benefit gained using statistical methods for obtaining cautious estimates for the various soil properties; the latter refers to the “characteristic value”, a concept commonly used in the Limit State analysis framework of Eurocode 7.
Keywords: Probabilistic analysis; Soil sampling location; Random Finite Element Method; Scale of fluctuation; Passive earth pressure; Optimal sampling location; Characteristic value